A Short Review of Lithium Ferrite Synthesis Techniques and Their Applications (International Journal of Scientific Research in Science and Technology, 2025)
Lithium ferrite (LiFe5O8, LiFe2.5O4) has emerged as a vital material in a variety of technological applications due to its unique magnetic, electrical, and chemical properties. This review presents a comprehensive examination of the synthesis techniques developed for lithium ferrite, ranging from conventional solid-state reactions to advanced methods such as sol–gel processing, hydrothermal synthesis, co-precipitation, and microwave-assisted techniques. Each method's advantages, limitations, and influence on the resulting ferrite's structural, morphological, and magnetic properties are critically discussed. Particular attention is given to how synthesis parameters such as temperature, precursor choice, and reaction atmosphere affect material performance. Additionally, this review explores the diverse applications of lithium ferrite across fields including microwave devices, magnetic storage media, sensors, catalysis, and biomedical engineering. Current challenges and future opportunities for optimizing lithium ferrite for next-generation applications are also outlined, providing a valuable framework for researchers aiming to tailor this material for specific functional uses.
Keywords: Lithium ferrite; synthesis techniques; different properties; technological applications